2018
DOI: 10.17503/agrivita.v40i0.1210
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of IBA and NAA Resulted in Better Rooting and Shoot Sprouting than Single Auxin on Malay Apple [Syzygium malaccense (L.) Merr. & Perry] Stem Cuttings

Abstract: This research aimed to study effects of IBA, NAA and their combination on rooting and shoot sprouting in Malay apple cuttings. Cuttings from superior genotype were collected and treated with (in ppm w/w): 0, 2000 IBA, 4000 IBA, 2000 NAA, 4000 NAA, 1000 IBA+1000 NAA, 2000 IBA+2000 NAA. To record the timing and percentage of rooting, cuttings were treated with (in ppm w/w) 1000 IBA+1000 NAA or without auxin as control. The results revealed that application of auxin was significantly enhanced root formation as sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
4
13
0
6
Order By: Relevance
“…From Table 1, it follows that a growth regulator most frequently used for the rooting of cuttings is IBA. Multiple studies [29,34,48,49], however, have produced results that, like ours, indicate that NAA either alone or in combination with IBA has a better influence on rooting. On the other hand, although the results of our comparisons of IBA at different concentrations showed greater success in rooting cuttings using mid-and higher-IBA concentrations, some other studies have shown lower concentrations to be more favorable [32,33,44].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…From Table 1, it follows that a growth regulator most frequently used for the rooting of cuttings is IBA. Multiple studies [29,34,48,49], however, have produced results that, like ours, indicate that NAA either alone or in combination with IBA has a better influence on rooting. On the other hand, although the results of our comparisons of IBA at different concentrations showed greater success in rooting cuttings using mid-and higher-IBA concentrations, some other studies have shown lower concentrations to be more favorable [32,33,44].…”
Section: Discussionsupporting
confidence: 61%
“…There are many methods of vegetative propagation of woody plants [22,27], including by means of rooted cuttings, which is affected by multiple factors [28]. This approach has continued to develop and is used particularly in growing cultivars of fruit and ornamental woody plants [29][30][31][32][33][34]. In forestry, it is important to maintain the uniformity of genetically significant characteristics, especially in establishing plantations of fast-growing woody species [24,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In present experiment, the influence of combined treatment of growth hormones for increasing shoot length, root length, number of primary roots and survival percentage is seen pronounced in comparison to individual hormonal treatment. The similar result was reported by Yusnita et al (2018) [19] in Syzygium malaccense (L.) Merr. & Perry stem cuttings with IBA 1000 ppm + NAA 1000 ppm, Umbreen et al (2019) [15] with IBA 1600 ppm + NAA 7000 ppm in Psidium guajava L., Hossain et al (2019) [8] in cuttings of Podocarpus neriifolius D. Don.…”
Section: Discussionsupporting
confidence: 90%
“…Dhatrika Rani et al (2018) working on guava, attributed the acceleration of photosynthesis activity to the increased leaf chlorophyll content due to increasing in leaf area by IBA treatment. Exogenous application of NAA and IBA is reported to enhance absorption activity of the roots (Yusnita et al, 2018). Accordingly, the high root biomass obtained in the present study might have helped in better water and nutrients uptake, which led to increasing leaf mineral content and leaf area, thus increasing the efficiency of the photosynthesis process, resulting in enhancing the different vegetative growth parameters studied in the presnt investigation.…”
Section: Discussion K-naa and Iba Effectmentioning
confidence: 54%